Design of Experiments Assessment for the Determination of Moisture Content in Five Herbal Raw Materials Contained in Tea Products - Luis Castillo; Eleaneth Baltodano; Nils Ramírez; Rolando Vargas; Georgia Hanley (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Research interest in natural raw materials is rapidly growing due to the high demand for natural products like herbal teas. Their quality control has a direct impact on safety and efficacy. The aim of this study was to evaluate the impact of sample’s mass and temperature on moisture content in Camellia sinensis (Black tea), Cassia fistula (Senna), Chamaemelum nobile (Chamomille), Lippia alba (Juanilama) and Tilia platyphyllos (Linden) with a gravimetric method developed through a full factorial 32 DoE. A response optimizer was executed in order to establish the test conditions that allow obtaining a response according to a target value from a certified method. DoE’s ANOVA shows reproducibility for Camellia sinensis, Cassia fistula, and Lippia alba. Also, the method’s model is able to explain the response variability for all samples based on the R2 (adj). The composite desirability for the proposed conditions of analysis for the five herbal materials is satisfactory according to each target value. However, the lack of reproducibility in Chamaemelum nobile and Tilia platyphyllos and also, the response prediction problems according to the R2 (pred) for Cassia fistula and Chamaemelum nobile, suggest the execution of further studies for them. Therefore, the present method is considered to be adequate for the analysis of moisture content in Camellia sinensis and Lippia alba raw herbs.